Money - Young, Robert, 1951- (Minneapolis : Carolrhoda Books, 1998)
Surveys the history, development, manufacture, and use of money in its various forms throughout the world.
Money, money, money -- All kinds of money -- Modern money -- We love money! -- Money magic.
Includes glossary and index.
School Library Journal.
Kirkus Review.
4.8
3-6
Keywords: Money -- Juvenile literature; Money; Money; Money